Pengaruh penanaman modal dalam negeri (PMDN), penanaman modal asing (PMA), ekspor dan impor terhadap pertumbuhan ekonomi Provinsi Jambi - Ningsih, Dian Setia; Haryadi, Haryadi; Hodijah, Siti (Jurnal Paradigma Ekonomika, 2020)
This study aims to analyze the development of PMDN, PMA, Exports, Imports, and Economic Growth in Jambi province and to analyze the influence of PMDN, PMA, Exports, and Imports on economic growth in Jambi province. The analysis model used is the Autoregressive Distributed Lag (ARDL). The results showed that in the short term PMDN had a significant negative effect on economic growth. PMA has a positive and significant effect on economic growth. Exports have a significant positive effect on economic growth. In the long term, PMDN has a positive and significant effect on economic growth. PMA has a negative and significant effect on economic growth. The export variable has a positive and significant effect on economic growth. And imports have a positive but insignificant effect on economic growth. It is hoped that economic growth will continue to increase from year to year, so the government must play an important role in increasing economic activities that have existing potentials so that the people's income is high which also reduces poverty and inequality that occurs.